0616 Retrospective Pain Reports in Obstructive Sleep Apnea Patients Relate to Age, Sex, BMI, Insomnia and Depression Scales, Not to Polysomnographic Measures of Sleep and Respiration. (25th May 2022) - Dubrovsky, Boris; Weingarten, Jeremy; Cunningham, John; Chen, Steven
Abstract: Introduction: OSA was found to alter pain experience, presumably due to apnea-related hypoxia and sleep disturbance. However, types of pain measures, demographic and subjective variables, such as mood, may influence pain experience in OSA. Presently, retrospective pain reports of patients referred for OSA evaluation were analyzed as a function of PSG measures, demographic variables, and self-reported mood and insomnia symptoms. Methods: On the evening of a diagnostic in-lab PSG, patients reported pain intensity in the preceding 6 months (PI, rage 0-10, Chronic Pain Grade Scale), symptoms of depression (Center for Epidemiologic Studies Depression Scale-Revised, CESDR) and insomnia (Insomnia Severity Index, ISI). PI was regressed on age, sex, BMI, total sleep time (TST), sleep stage percentages, sleep efficiency, WASO, awakenings, respiratory arousal index, AHI, SpO2% nadir, time below SpO2 90%, desaturation index, CESDR and ISI using a stepwise entry. Results: A total of 1293 patients with ≥2 hours of PSG-defined sleep completed the questionnaires; 3% Asian, 42% black, 5% Hispanic, 32% white; 62% women; 66% had OSA (AHI≥5); Mage=58.7±13.8, MBMI=33.8±7.3, MPI=3.5±3.1; MISI=12.9±6.9; MCESDR=14.7±13.1, MAHI=17.6±22.9, MSpO2%nadir=84.9±9.0. Higher PI was associated with female sex (p<0.001, R2=2.6%), older age (p<0.001, R2=3.7%), higher BMI (p<0.001, R2=2.5%), higher ISI (p<0.001, R2=4.5%), higher CESDR (p<0.001, R2=2.3%) and longer TST (p=0.028, R2=0.4%). No other sleep or respiratory variables related to PI. No significant interactions with AHI≥5 were present. No differences between OSA (AHI≥5) and no-OSA groups were present on PI, ISI or CESDR after controlling for age, sex and BMI. Conclusion: Retrospective reports of pain intensity were unrelated to PSG measures of sleep and respiratory disturbance. Female sex, older age and higher BMI related to higher PI regardless of the OSA diagnosis and collectively accounted for 8.8% of the PI variance. Symptoms of insomnia and depression related to higher PI independently of OSA, accounting for 4.5% and 2.3% of the PI variance, respectively. As in prior research OSA was associated with insomnia and depression, these variables may mediate the relationship between OSA and pain. Support (If Any): None